2020
DOI: 10.3390/ijms21207521
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Amino Acid Substitutions in a Trichoderma Peptaibol Confer Activity against Fungal Plant Pathogens and Protect Host Tissues from Botrytis cinerea Infection

Abstract: Fungal species belonging to the Trichoderma genus are commonly used as biocontrol agents against several crop pathogens. Among their secondary metabolites, peptaibols are helical, antimicrobial peptides, which are structurally stable even under extreme pH and temperature conditions. The promise of peptaibols as agrochemicals is, however, hampered by poor water solubility, which inhibits efficient delivery for practical use in crop protection. Using a versatile synthetic strategy, based on green chemistry proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 60 publications
3
48
0
1
Order By: Relevance
“…were designed and synthesized to increase the water solubility and antifungal activity against an economically important fungal plant pathogen, Botrytis cinerea . These molecules have single amino acid substitutions, predominantly Gly/Lys located inside a helical structure [ 55 ]. It was shown that this modification increased peptide amphiphilicity and did not lead to critical changes of 3D orientation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…were designed and synthesized to increase the water solubility and antifungal activity against an economically important fungal plant pathogen, Botrytis cinerea . These molecules have single amino acid substitutions, predominantly Gly/Lys located inside a helical structure [ 55 ]. It was shown that this modification increased peptide amphiphilicity and did not lead to critical changes of 3D orientation.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed resistance to fluconazole and intraconazole and low susceptibility to caspofungin. Among the clinically approved antifungal drugs, only amphotericin B displays a comparable activity profile towards the drug-resistant C. neoformans and C. laurentii isolates obtained from HIV-positive patients with cryptococcal meningitis [ 28 , 31 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present study has been designed to test the possible use of small antimicrobial peptides (AMPs), called “peptaibols,” as biopesticides to control rice blast disease caused by P. oryzae . Recently, water-soluble analogs of the T. longibrachiatum short-length peptaibol trichogin GA IV ( Szekeres et al, 2005 ) have been synthesized using a versatile synthetic strategy designed to reduce the impact on the environment ( De Zotti et al, 2020 ). Three of these analogs completely inhibited the growth of Botrytis cinerea in vitro at low micromolar concentrations, and the most effective peptides significantly reduced gray mold symptoms on common bean, grapevine leaves and ripe grape berries ( De Zotti et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We recently found that water-soluble peptaibol analogs, featuring Gly-to-Lys substitutions, possess anticancer activity [6]. Besides, through the application of a biorational approach, we recently designed water-soluble peptaibol analogs with improved bioactivity against fungal plant pathogens [9].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of peptaibols is not trivial, as the steric hindrance of Aib makes it poorly reactive. Nonetheless, we have recently proposed an effective, ecofriendly strategy [9] that we are also applying here. Such a procedure for the synthesis of peptaibols is also less expensive than the standard protocol, and represents a step forward towards the translation of peptaibols to the market; however, it did not solve the main problem connected with the production of peptaibols: the presence of a C-terminal aminoalcohol (featured in the natural sequences), that forces the use of costly, preloaded resins for their production by solid-phase peptide synthesis [10].…”
Section: Introductionmentioning
confidence: 99%